Pengaruh Jenis Kemasan dan Lama Penyimpanan terhadap Mutu Bubuk Andaliman - Sitohang, Apul; Marbun, Baang Soyun (Universitas Katolik Santo Thomas Medan, 2020)
This study aims to determine the effect of packaging types and storage duration on the quality of andaliman powder. The study was conducted at the Laboratory of Processing and Management of Agricultural Products, Agricultural Product Technology Study Program, Faculty of Agriculture, Catholic University of St. Thomas Medan. This research was conducted using Factorial Complete Random Design method. The first factor is packaging with a password (K), consisting of 4 types, namely: K1 is Glass bottle, K2 is Plastic bottle, K3 is Flip plastic and K4 is Paper. The second factor is the storage time with L code which consists of four levels, namely: L0 is 0 weeks, L1 is 2 weeks, L2 is 4 weeks and L3 is 6 weeks. The results showed that the type of packaging had a very significant effect on water content, total acid, oleoresin content and organoleptic value, but it was not significant for ash content. The highest water content, ash content and total acid were found in paper plastic packaging, while the lowest was in glass bottle packaging, while the highest oleoresin content and highest organoleptic value were found in glass bottle packaging, while the lowest was on paper packaging. Storage time has a very significant effect on water content, total acid, oleoresin content and organoleptic value, but not significant to ash content. The longer the storage, the moisture content, ash content and total acid content increase, while the oleoresin content and organoleptic values decrease. The interaction between the type of packaging and storage duration gave no significant effect on water content, ash content, total acid, oleoresin content and organoleptic value. The best quality of andaliman powder is obtained in the type of glass bottles and plastic bottles which can be seen from the water content, oleoresin content and organoleptic value.Â Â